Control of a robotic arm with a BCI system, using brain signal processing - Coronado Bautista, Javier (2021)
The need to develop a BCI brain- computer interface system for the   control   of   a   robotic   arm   in   Peru   arises   from   the   possibility   of interconnecting the human nervous system with a robotic or mechatronic system, and using this concept to recover some motor function.   Brain   Computer   Interface   (BCI)   is   a   communication   system  based  on  the  recording  of  brain  signals  (EEG).  The electroencephalogram is the basis and support of the BCI technology. It is a novel technology that allows human-machine interaction in a virtual or physical environment, through a communication channel between the central nervous system and a robotic device. In recent years,  the  aforementioned  systems  have  caused  the  interest  of important research centers worldwide.